(untitled) (UCC Law Journal, 2024)
This article discusses the resurgence of military coup d’états, in Africa, whether it is backward or forward movement in democratic governance on the continent. Recently there has been an upsurge in UCG in Mali, Burkina Faso, Sudan, Guinea and the latest now is Gabon. This trend is against Article 4(m) (p) of the Constitutive Act of African Union that condemns UCG; and the African Charter on Democracy, Election and Good Governance (ACDEGG), 2007. It is not also a surprise that some citizens of these countries where the unconstitutional change of government has taken place were found jubilating due to maladministration of the constitutionally elected leaders. This article aims at bringing the attention of global leaders to the regressive trend in the democratic progress of certain African nations. Doctrinal methodology is used and the data method is content analyses. The findings of the study show that some citizens of these countries are not enjoying dividends of democracy and that the military itself has not imbibed the dictates of civilian administration or rule on the continent. This paper concludes that the mere suspension of a particular country whose civilian administration has been overthrown is not enough deterrent to other countries in Africa, and stricter penalties is needed to be implemented against such country. It is one of the recommendations of this article that paper condemnation of illegal take over government and the suspension of such a country from AU is not enough deterrent to putsch in the continent.